MANAGEMENT OF EDUCATION MARKET AND INTELLECTUAL SOCIAL SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the current problems in the educational market of Uzbekistan. During the foundation for the third renaissance period, proposals for the solution of these problems were presented. The causes of the factors that negatively affect the quality of trained personnel in the field of general secondary and higher education are indicated. The status of the teacher in improving the quality of education and the demands placed on him were studied on the basis of historical evidence. The author gave his conclusions citing the lectures of the President of the Republic of Uzbekistan Shavkat Mirziyoyev and the monographs of scientists conducting scientific research in this field.